EVALUASI PROGRAM PERCEPATAN/AKSELERASI BELAJAR DI SD MUHAMMADIYAH SAPEN YOGYAKARTA - Ofianto, Ofianto (Pusat Kajian Humaniora FBS Universitas Negeri Padang, 2015)
This study aims to explore the feasibility of information about an accelerated program at the Muhammadiyah Sapen elementary school Yogyakarta, to describes empirically as well evaluating the implementation of an accelerated program about. This research can be categorized as an evaluative research with a qualitative approach.Data were collected through interviews, observation and studying documents, then analyzed inductively and constantly through categorization, classification, and reduction. The subjects were the school principals, chief of acceleration program, teachers, parents and participants of the acceleration program. The results showed that the selection of program participants has not fully meet the established criteria. Each student must pass four selections; the selection of objective data, subjective assessment, health requirements, and students readiness and parents support. The four aspects has not been done properly, particularly aspects of objective data assessment. Selection of teachers has not been conducted based on the criteria. Teachers are still determined by the principal and teaching experience is ignored. For the curriculum, funding and infrastructure already fulfill the criteria.Keywords: evaluation, accelerated learning program, elementary school